Facile and Cost Effective Synthesis of Oxide-Derived Silver Catalyst Electrodes via Chemical Solution Deposition for CO2 Electro-Reduction - Nursanto, Eduardus Budi; Won, Da Hye; Jee, Michael Shincheon; Kim, Haeri; Kim, Nak-Kyoon; Jung, Kwang Deog; Hwang, Yun Jeong; Min, Byoung Koun (SPRINGER/PLENUM PUBLISHERS, 2018)
Electrochemical CO2 reduction to useful fuels is a promising strategy for the sustainable energy production. However, because CO2 reduction reaction involves sluggish kinetics, the development of high performing catalyst is a first priority for the success in this system. Herein, cost effective fabrication of oxide-derived silver catalyst for CO2 electro-reduction was successfully prepared by simple chemical solution deposition involving the following steps: (i) spin-coating of precursor solution, (ii) oxidation by air-annealing, and (iii) electrochemical reduction. The prepared silver catalyst achieved 83.7% of CO Faradaic efficiency at - 1.19 V-RHE with an outstanding mass activity of 465.04 A g(-1) which was originated from the unique features of the catalyst as well as precursor solution. With the introduced fabrication method, the precursor solution containing relatively low silver concentration was preferred to form small silver particles, resulting in high catalytic activity. We anticipate the developed method to be widely applied for the preparation of oxide-derived metal catalysts and metal alloy nanostructured catalysts in advanced CO2 conversion system.
Keywords: CARBON-DIOXIDE; ELECTROCATALYTIC REDUCTION; ELECTROCHEMICAL REDUCTION; SURFACE CHARACTERIZATION; SELECTIVE CONVERSION; EFFICIENT; ELECTROREDUCTION; AG; STABILITY